Moral Values in Novel 3600 Detik: Literary Pragmatics Study - Ritanto Ilahi; Suhirman Suhirman; Heny Friantary (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
The problem raised in this study is how the form of delivery of moral values ​​used by the author, the moral values ​​contained in the main character in dealing with problems and the form of moral values ​​contained in the novel 3600 Detik by Charon. The purpose of the study is to describe the form of conveying moral values ​​used by the author, the moral values ​​contained in the main character in dealing with life's problems and the form of moral values ​​contained in the novel 3600 Detik by Charon. The approach used in this research is a theoretical approach (literary pragmatic theory) and methodological approach (qualitative descriptive approach), and is studied using literary pragmatic studies. The method uses content analysis method. The data source is the novel 3600 Seconds by Charon. The data collected is in the form of words or quotes. Data collection techniques in the form of library techniques. Data validity techniques are focused on two ways, namely increasing persistence and using reference materials. The results of the study concluded that the form of moral delivery consists of two components, namely direct delivery which is conveyed through the author's description and through characters and indirect delivery which is conveyed through events and conflicts in the novel 3600 Detik. The moral values ​​contained in the main character in dealing with life's problems in the 3600 Seconds novel consist of five variants, namely disobeying school rules, caring for friends, never giving up, being firm and being honest. The form of moral values ​​contained in the 3600 Seconds novel consists of three aspects, namely the form of moral values ​​in human relations with God, forms of moral values ​​in human relations with humans and forms of moral values ​​in human relations with oneself.